2014
DOI: 10.3892/ijo.2014.2571
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-194 suppresses osteosarcoma cell proliferation and metastasis in vitro and in vivo by targeting CDH2 and IGF1R

Abstract: Studies have shown that miR-194 functions as a tumor suppressor and is associated with tumor growth and metastasis. We studied the effects of miR-194 in osteosarcoma and the possible mechanism by which miR-194 affected the survival, apoptosis and metastasis of osteosarcoma. Both human osteosarcoma cell lines SOSP-9607 and U2-OS were transfected with recombinant lentiviruses to regulate miR-194 expression. Overexpression of miR-194 partially inhibited the proliferation, migration, and invasion of osteosarcoma c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
68
0
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(73 citation statements)
references
References 50 publications
4
68
0
1
Order By: Relevance
“…Data from a previous study suggested that OS progression is associated with downregulation of miR-143 expression and that the pro-apoptotic function of miR-143 was suppressed by this downregulation, leading to increased expression of Bcl-2, an important anti-apoptotic molecule involved in cell survival [Zhang et al, 2010]. In addition, miR-194 was also downregulated in OS, and overexpression of exogenous miR-194 in OS cells reduced the levels of insulinlike growth factor I receptor (IGF1R) and N-cadherin, thus inhibiting proliferation, migration, and invasion of OS cells [Han et al, 2014]. In this context, miR-150 expression in OS has not been investigated, and the mechanisms involving miR-150 in OS progression remain unknown.…”
Section: © 2015 S Karger Ag Baselmentioning
confidence: 99%
“…Data from a previous study suggested that OS progression is associated with downregulation of miR-143 expression and that the pro-apoptotic function of miR-143 was suppressed by this downregulation, leading to increased expression of Bcl-2, an important anti-apoptotic molecule involved in cell survival [Zhang et al, 2010]. In addition, miR-194 was also downregulated in OS, and overexpression of exogenous miR-194 in OS cells reduced the levels of insulinlike growth factor I receptor (IGF1R) and N-cadherin, thus inhibiting proliferation, migration, and invasion of OS cells [Han et al, 2014]. In this context, miR-150 expression in OS has not been investigated, and the mechanisms involving miR-150 in OS progression remain unknown.…”
Section: © 2015 S Karger Ag Baselmentioning
confidence: 99%
“…Therapeutic strategies for osteosarcoma include wide tumor excision, radiotherapy, and multi-agent chemotherapy, all of which have significantly improved the prognosis of patients with osteosarcoma [29,30]. However, patients with osteosarcoma showed a very poor cure rate, and the majority of patients eventually died from complications related to pulmonary metastases [31].…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies suggest that miR-194 is considered as a tumour suppressor and its targets were identified in many cells and tissues. For example, Han et al demonstrated that overexpression of miR-194 significantly repressed the proliferation, migration, and invasion of osteosarcoma cells in vitro, as well as tumour growth and pulmonary metastasis in vivo by targeting cadherin-2 (CDH2) and insulin-like growth factor 1 receptor (IGF-1R) [12]. In addition, it has been reported that miR-194 inhibited the EMT of EC cells [14] and gastric cancer cells [18].…”
Section: Discussionmentioning
confidence: 99%
“…A growing number of studies have confirmed that miRNAs are differentially expressed in pneumonia, and many of them have been considered as biomarkers of pneumonia [7][8][9]. Among the miRNAs, miR-194 has been widely studied in various cancer cells, and shows complicated functions in regulating cell differentiation [10], cell migration [11], cell proliferation, apoptosis [12], and invasion [13]. For example, Dong et al suggested that miR-194 inhibited epithelial to mesenchymal transition (EMT) of endometrial cancer (EC) cells by targeting oncogene B-cell-specific Moloney murine leukemia virus insertion site 1 (BMI-1) and inhibition of BMI-1 by miR-194 may have therapeutic potential in suppressing EC metastasis [14].…”
Section: Introductionmentioning
confidence: 99%